Reliable software technologies - Ada-Europe 2011 16th Ada-Europe international conference on reliable software technologies, Edinburgh, UK, June 20-24, 2011 : proceedings - Romanovsky, Alexander; Vardanega, Tullio (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 16th Ada-Europe International Conference on Reliable Software Technologies, Ada-Europe 2011, held in Edinburgh, UK, on June 20-24, 2011. The revised 12 papers presented together with several invited contributions were carefully reviewed and selected from 30 submissions. Topics of interest to the conference are methods and techniques for software development and maintenance; software architectures; enabling technologies; software quality; theory and practice of high-integrity systems; embedded systems; mainstream and emerging applications; experience reports; the future of Ada.